Chapter Italo Calvino - Falaschi, Giovanni (Firenze University Press, 2025)
This essay considers Calvino’s work as a journalist, editor and writer. It also studies various figures of workers in the writer’s works, first of all the factory worker. And finally the ideological debate on the working class in the age of neo-capitalism.